Investigations of Renin-Angiotensin Aldosterone System (RAAS) genes in hypertrophy in hypertrophic cardiomyopathy (HCM) founder families - Cloete, Ruben Earl Ashley (Stellenbosch : Stellenbosch University, 2012)
Thesis (MScMed)--Stellenbosch University, 2008.